2022
DOI: 10.31557/apjcp.2022.23.6.2057
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes, and Barriers (KABs) of Regarding Colorectal Cancer Screening among the Population of the Republic of Kazakhstan

Abstract: Background: One of the obstacles to participating in CRC screening is the lack of knowledge about the importance of CRC, its risk factors and the benefits that can be obtained through screening. The aim of this study was to evaluate the awareness and to identify the barriers to colorectal cancer screening among the population of the Republic of Kazakhstan. Methods: This is a cross-sectional study based on questionnaire, which was conducted in different regions of Kazakhstan from 2020 to 2021. This study involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
(28 reference statements)
1
2
0
Order By: Relevance
“…Furthermore, we found that participant fears that screening method procedures would be painful and/or embarrassing constituted the most reported. In parallel, previous studies conducted in countries such as the United States, the Republic of Kazakhstan, Lebanon, and Saudi Arabia supported our findings that the most reported reasons for the attitudes toward CRC screening were uncomfortable, painful, or embarrassing (Alaqel et al., 2021; Al‐Thafar et al., 2017; Jillson et al., 2015; Tfaily et al., 2019; Toleutayeva et al., 2022). Similarly, a systematic review of the literature has revealed that fear commonly acted as a barrier to participation in CRC screening (Honein‐Abou Haidar et al., 2016).…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, we found that participant fears that screening method procedures would be painful and/or embarrassing constituted the most reported. In parallel, previous studies conducted in countries such as the United States, the Republic of Kazakhstan, Lebanon, and Saudi Arabia supported our findings that the most reported reasons for the attitudes toward CRC screening were uncomfortable, painful, or embarrassing (Alaqel et al., 2021; Al‐Thafar et al., 2017; Jillson et al., 2015; Tfaily et al., 2019; Toleutayeva et al., 2022). Similarly, a systematic review of the literature has revealed that fear commonly acted as a barrier to participation in CRC screening (Honein‐Abou Haidar et al., 2016).…”
Section: Discussionsupporting
confidence: 88%
“…In the Republic of Kazakhstan, Toleutayeva et al found similarly low levels of knowledge among the general population [ 31 ], further supporting the argument that knowledge deficits are a common barrier to effective CRC screening worldwide. This consistency across diverse geographical and cultural contexts highlights the universal challenge of educating the public about cancer prevention and screening.…”
Section: Discussionmentioning
confidence: 83%
“…Despite recent progress in treatment and cancer diagnostics, malignant neoplasms remain the second leading cause of death in both men and women (Price et al, 2020). Barriers to cancer screening are associated with socioeconomic and psychological factors, or poor accessibility (Toleutayeva et al, 2022).…”
Section: Introductionmentioning
confidence: 99%